Religious Legitimacy and Extractive Politics: The Disarticulation of Human Security in Indonesia’s Mining Concessions - Zarkasyi, Fajar Imam; Reynaldi, Dwiki Yulian; Shafar, Wildan Ilmanuarif (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2026)
This study examines how religious legitimacy shapes and reorders human security discourse within policies granting mining concessions to religious organizations in Indonesia. It departs from the growing involvement of religious actors in extractive sectors and the resulting implications for the protection of people, the environment, and affected communities. Using a qualitative approach grounded in critical discourse analysis and the hegemony theory of Ernesto Laclau and Chantal Mouffe, the study analyzes state statements, elite pronouncements from religious organizations, and national media discourse through systematic coding and relational mapping with NVivo. The findings show that religious concepts—most notably maslahat—operate as a hegemonic nodal point that binds claims of development, welfare, moral obligation, and nationalism into a single chain of equivalence that stabilizes mining concession policies. Within this configuration, human security is not explicitly rejected; rather, it becomes disarticulated and reduced to technical and procedural concerns through the normalization of ecological risks, livelihood vulnerabilities, and social impacts as routine consequences of development. Furthermore, the involvement of religious organizations marks a transformation of religious roles from moral guardians to extractive actors through a mechanism of antagonism displacement, whereby structural conflicts between the state and citizens shift into internal moral debates within organizations. Theoretically, this study affirms that human security constitutes a contested discursive arena rather than a neutral normative framework. It contributes to extractive politics scholarship by demonstrating how religious authority can function as a hegemonic mechanism that stabilizes extractive development while marginalizing ecological and social protection.